De l’éruption rhétorique : étude de l’hypotypose dans la littérature catastrophique franco-antillaise - Vignoli, Alessia (Acta Universitatis Lodziensis. Folia Litteraria Romanica, 2018)
Hypotyposis is a figure of speech which often appears in written descriptions of natural disasters (e.g. in Voltaire’s Poem on the Lisbon disaster, 1756). Its ability to show in the eye of the reader the unfolding of a tragic event through a vivid and dynamic description makes hypotyposis a useful tool in catastrophic and post-apocalyptic fiction. The aim of this contribution is to study the presence and function of hypotyposis in three novels which belong to French Caribbean literature, concerning two volcanic eruptions that took place in the 20th century (Montagne Pelée, Martinique, in 1902 and Soufrière, Guadeloupe, in 1976). By a stylistic and thematic analysis of some selected texts from Raphaël Tardon’s La Caldeira (1948), Raphaël Confiant’s Nuée ardente (2002) and Daniel Maximin’s Soufrières (1987), we will focus on the role of hypotyposis as a creator of pathos and emotional reactions in the reader’s mind by which the author can also convey a social and political message.